Exploring the ecological assets of Tunas Mekar Project’s graduate entrepreneurs - Siti Hajar Kamaruddin,; Siti Munirah Mauzud,; Nor Azrul Mohd Zin, (Penerbit Universiti Kebangsaan Malaysia, 2019)
Entrepreneurship has been one of the alternatives in overcoming the unemployment rate among the youths that graduated from the higher learning institutions in Malaysia. Various efforts and policies have been developed to increase the participation of graduates in the entrepreneurial field. Nevertheless, statistics show that the participation of graduates in this field is still unsatisfactory. There are two youth development assets that influence the ability of graduates to start a business, known as the individual asset and the ecological asset. This research seeks to explore the ecological assets which influence the ability of graduates to start a business based on their entrepreneurial experiences. This research is a qualitative single case study research using purposive sampling. A total of 12 graduate entrepreneurs from the Tunas Mekar Project had been chosen as the research informants. Research data has been collected through the conduct of in-depth and semi-structured interviews, non-formal observations and document analysis, in which the data were later analysed using the Atlas.ti (Version 8) computer software. The findings of the research showed that social network support, monetary network support, and a positive entrepreneurship ecosystem have helped graduates to start a business after they participated in the Tunas Mekar Project. It is observed that all three assets have helped to increase the capacity of the graduates to overcome the challenges in initiating a business. Thus, everyone has to play a role in increasing and strengthening the entrepreneurship potential within the graduates. It is hoped that the various initiatives and support given to this group will produce more graduate entrepreneurs, which will also help to overcome the problem of unemployment among the highly educated youths in the future.